Development of Relations Between Canadian and American National Trade Unions Centers – 1886-1925 - Williams, C. (Relations industrielles / Industrial Relations, 1965)
In this paper, the author explains how the relationships between Canadian and American trade union centers have developed. Up to the year 1897, there was no continuous relation between union organizations of both countries. The new binational policy adopted by the majority of the TLC delegates at its 1902 convention brought-forth the split in the Canadian labor movement.The unions expelled from the TLC founded the NTLC which became the CFL in 1908. When the latter disappeared in 1927, the French Canadian labor movement was about the only one to maintain its opposition to the American influence.